Investigasi resistensi Anopheles sp. terhadap insektisida piretroid dan kemungkinan terjadinya mutasi gen voltage gated sodium channel (VGSC) - Haryanto, Didid; Dalilah, Dalilah; Anwar, Chairil; Prasasti, Gita Dwi; Handayani, Dwi; Ghiffari, Ahmad (Perhimpunan Entomologi Indonesia, 2018)
Extensive and continuous use of pyrethroid insecticides to prevent the transmission of malaria can lead to mutations in the voltage gate sodium channel gene (VGSC) in mosquito vectors. This gene mutation associated with insensitivity pyrethroid is known as knockdown resistance (kdr). The emergence of resistance to pyrethroid insecticides in vector mosquitoes can be a barrier to the successful termination of malaria transmission. Therefore, detection of mutation is necessary to prevent the resistency from build up. The aim of the study was to determine the resistance status of pyrethroid insecticides and identify mutations in the VGSC gene codon 1014 marker for resistance to Anopheles sp. which is a malaria vector in South Sumatra Province. Samples were taken from three districts in South Sumatra: Muara Enim, OKU, and Lahat. The susceptibility enzymatic test of pyrethroid insecticide (permethrin 0.75%) was preliminarily carried out according to WHO 2016 standard on Anopheles vagus Dí¶nitz species. Identification of VGSC gene mutation was performed on all An. vagus that were previously tested for susceptibility and on An. barbirostris van der Wulp species using seminested-PCR and followed by sequencing. The result showed that samples from Muara Enim regency had resistance, whereas in Lahat and OKU regencies were still susceptible to permethrin. From the sequence analysis it is shown that there are no change in DNA kdr bases in VGSC gene insecticide target sites from all regencies. In conclusion, based on molecular studies, there were no pyrethroid insecticide resistance in South Sumatra Province.